Direct Access to Fluorinated Thiadiazolo[3,2-a]pyrimidin-7-one Systems - Silpa, Laurence; Petrignet, Julien; Abarbri, Mohamed (Synlett, 2014)
A mild, simple method for the regioselective synthesis of thiadiazolo[3,2-a]pyrimidin-7-ones bearing a perfluoroalkyl group is reported. In order to study the core reactivity, various nucleophile substitutions were performed involving the reactive carbon–bromide bond via a one-pot strategy.
Keywords: regioselectivity; one-pot synthesis; fluorinated thiadiazo[3,2-a]pyrimidin-7-ones; nucleophile substitution